Pulmonary blood supply in bidirectional cavopulmonary anastomosis with pulsatile pulmonary blood flow: quantitative analysis using radionuclide angiocardiography - Reich, O; Horváth, P; Ruth, C; Krejcír, M; Skovránek, J (Heart (British Cardiac Society), 1996)
OBJECTIVE: To establish a non-invasive method for quantitative analysis of pulmonary perfusion in patients with bidirectional cavopulmonary anastomosis (BCPA) and sources of pulsatile blood flow. The method should quantify left to right lung flow ratio and relative contribution of BCPA and sources of pulsatile blood flow to perfusion of each lung. DESIGN: A pilot study using radionuclide angiocardiography for quantitative analysis and for visualisation of cavo-caval collaterals. No criterion standard is available. SETTING: Tertiary care centre, ambulatory and hospital inpatient care. PATIENTS: Consecutive sample of 18 patients with BCPA and sources of pulsatile blood flow. RESULTS: In eight patients (44%) cavocaval collaterals prevented quantitative analysis. In 10 patients without cavo-caval collaterals, BCPA provided 42.3 (SEM 3.4)% of total pulmonary blood flow. From the total BCPA flow, 67.2 (4.3)% was directed to the ipsilateral lung. This lung received only 16.5 (3.3)% of all the blood from sources of pulsatile blood flow. The blood flow to the lung at the side of BCPA accounted for 35.3 (1.7)% of the total pulmonary blood flow. CONCLUSIONS: Radionuclide angiocardiography allows the quantitative analysis of pulmonary blood supply in BCPA with sources of pulsatile blood flow except in patients with cavo-caval collaterals or bilateral BCPA. Non-pulsatile flow from BCPA is mainly directed to the ipsilateral lung, whereas pulsatile flow to the contralateral lung. Total perfusion of the ipsilateral lung is less than the perfusion of the contralateral lung.
Keywords: Treatment Failure; Perfusion; Child, Preschool; neúspěšná terapie; bypass pravého srdce; plíce; Child; pilotní projekty; dítě; Adult; vrozené srdeční vady; dospělí; radioisotopová angiografie; Heart Bypass, Right; pulzatilní průtok; Lung; předškolní dítě; lidé; Humans; perfuze; Heart Defects, Congenital; Pulsatile Flow; Pilot Projects; Radionuclide Angiography